Application-Based Siger Tourism Design As a Solution Program for Tourism Development in Post-Pandemi Lampung Province - SAEPUDIN, Saepudin; RAHMAWATI, Rahmawati; PRATIWI, Ajeng (Journal of Tourism Economics and Policy, 2023)
Tourism is one of the most important economic sectors in Indonesia, this is evidenced by the large number of domestic and foreign tourists who come to visit Indonesia, according to data from the Indonesian Central Bureau of Statistics in September 2019 there were 1,388,719. However, after the COVID-19 pandemic, the number of tourist visits decreased by -88.95%, where as of September 2020, according to the Central Bureau of Statistics, the number of foreign tourists was only 153,498. Siger Tourism is an android-based application that aims to assist the Lampung Provincial government in attracting interest and increasing the number of tourism visits which have decreased significantly after the COVID-19 pandemic. In addition, this program also aims to help local MSMEs around tourist sites and in the Province. Lampung. This scientific writing uses a qualitative method that is literature study, namely the technique of collecting data and information through various literature or references. Siger Tourism as a tourism application media that is suitable for use by the community because it provides information about tourism and also introduces the history of these tourist attractions as an educational event for tourists. Siger Tourism has several features, namely log in menus, tourist destinations, restaurants, markets, lodging, maps and call center features. So that this can help tourists, MSME actors, and the government to increase the economic value of the community. The Siger Tourism design is a tourism development solution program in the province of Lampung during the post-pandemic period.